Scaling of turbine metal temperatures in cooled compressible flows-experimental demonstration of a new theory - Luque, S; Jones, T; Povey, T (American Society of Mechanical Engineers, 2017)
Experimental measurements of overall cooling effectiveness conducted on a high-pressure turbine vane in a warm rig flow are scaled to engine conditions in this paper. A new theory for the scaling of turbine metal temperatures in cooled compressible flows has been applied, based on the principle of superposition, and demonstrated analytically and numerically in a previous paper. The analysis employs a definition of overall cooling effectiveness based on a new recovery and redistribution temperature, which makes it independent of the temperature boundary conditions of the hot and cold flow streams. This enables the vane external wall temperatures to be scaled to engine conditions by varying, in a fixed aerodynamic field, the mainstream-to-coolant temperature ratio. Experimental validation of the theory is provided in this article. Measurements were conducted in the Annular Sector Heat Transfer Facility, which employs fully cooled nozzle guide vanes, production parts of a civil aviation engine currently in service. Mainstream Mach and Reynolds numbers, inlet turbulence intensity, and coolant-to-mainstream total pressure ratio (and thus momentum flux ratio) are all matched to engine conditions. Fullcoverage overall cooling effectiveness distributions, acquired by infrared thermography, are presented for a range of mainstream-to-coolant temperature ratios between 1.05 and 1.22 and subsequently scaled to engine conditions by an iterative procedure. In reducing to practice the principles of the new scaling theory, it is demonstrated that direct validation of turbine cooling system performance is possible in experiments at lower than engine temperatures.